2009
DOI: 10.1161/strokeaha.108.542894
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Stroke Incidence and Poststroke Disability in the Framingham Heart Study

Abstract: Background and Purpose-Stroke is emerging as a major public health problem for women, as it is for men. Controversy persists regarding gender differences in stroke incidence, severity, and poststroke disability. Methods-Participants in the Framingham Original (nϭ5119; 2829 women) and Offspring (nϭ4957, 2565 women) cohorts who were 45 years and stroke-free were followed to first incident stroke. Gender-specific outcome measures were adjusted for the Framingham Stroke Risk Profile components. Results-We observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

49
426
12
18

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 571 publications
(505 citation statements)
references
References 44 publications
49
426
12
18
Order By: Relevance
“…A basic question, especially concerning age, is whether the apparent associations are due to ageing itself or secondary to other causes. Regarding sex, previous researchers have generally reported a negative effect of female sex on functional outcome 5, 19, 20, 21, 22, 23, 24, 25, 26, 27. This is seen also in the present study (for details, see11).…”
Section: Discussionsupporting
confidence: 86%
“…A basic question, especially concerning age, is whether the apparent associations are due to ageing itself or secondary to other causes. Regarding sex, previous researchers have generally reported a negative effect of female sex on functional outcome 5, 19, 20, 21, 22, 23, 24, 25, 26, 27. This is seen also in the present study (for details, see11).…”
Section: Discussionsupporting
confidence: 86%
“…Although this study's findings could not establish a causal relationship between breastfeeding and risk of stroke, health disparities surrounding stroke1, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 and breastfeeding rates52, 53, 54 persist. Stroke is 1 of the leading causes of death among Hispanic and non‐Hispanic black women over 65 2, 4.…”
Section: Discussioncontrasting
confidence: 62%
“…Stroke costs the nation $34 billion annually including the cost of healthcare services, medications, and lost productivity 1. Approximately 55 000 more US women than men suffer from a stroke annually 1, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16. Compared with elderly men, elderly female stroke survivors are also at increased risk for moderate to severe disability, poorer quality of life, and institutionalization 16, 17…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that men have higher stroke incidence than women in younger and middle‐age groups, but these differences narrow in older age groups and reverse in the elderly 11, 12, 13, 14, 15, 16. Recent studies have suggested declining stroke incidence in both men and women.…”
Section: Introductionmentioning
confidence: 99%